Determination of Optimal Rain Gauge on The Coastal Region Use Coefficient Variation: Case Study in Makassar - Giarno Arno; Muflihah Muflihah; Mujahidin Mujahidin (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2021)
The quality of rainfall data is highly significant in disaster analysis, ecology, and water resource management. However, the accuracy and quantity of rain gauges are often inadequate, especially for analyzing extreme events, including the Makassar City flood, in 2019. This inadequacy is due to several reasons, including rain gauges’ inadequacy and insufficient distribution. This study, therefore, aims to analyze the requirements of optimal rain gauges, using coefficients of variation in various error levels, based on the latest rainfall data in several locations within Makassar City. Monthly and yearly rainfall observation data from 2010 to 2019 obtained at 5 locations were used to calculating the optimal rain gauge number. According to the results, the existing station has a 10% and 15% monthly and annual error, respectively. This region has 3 groups causing highly optimal rain gauges, and these are the first group comprising Paotere, Panaikang, as well as Biring Romang, while the second and third groups comprise Sudiang and Barombong. The northwest wind blows towards the coast and crosses these three places in a line, thus, causing rainfall intensity with a slight disparity, between the first group. Furthermore, the combination of these places resulted in low optimal rain gauge. However, the combination of the first group with the second and third lead to an increase in the optimal rain gauge number. The low elevation, proximity, and location of the first group’s three locations in line with the rain-causing wind results in low optimal rain gauge. In the combination of the first, second, and third groups, additional gauges are required to obtain a 5% or 10% error. The rainfall intensity and position greatly influence the rain catchment in Makassar, and consequently, the optimal rain gauge number. In addition, the distance, topographical aspects, and the combined land-sea and monsoonal winds’ factors must also be analyzed, in deploying equipment.